Negotiating Religious Identity in Private Space: A Phenomenological Study of Interfaith Married Couples - Susanto, Susanto; Salik, Yunus (LPPM IAIN Kudus, 2025)
This phenomenological study deeply reveals the subjective experiences of interfaith couples in Tana Toraja in negotiating religious identities in private spaces. The findings highlight that negotiation is a dynamic process influenced by awareness of differences, adaptation strategies, the socio-cultural context of Tana Toraja, and the formation of subjective meaning. Factors driving interfaith marriages include freedom to choose a partner, feelings of liking and love, and sometimes a lack of understanding of religion. The main implications touch on spiritual principles, with concerns about potential conflict. However, successful negotiation is based on a commitment to mutual respect, active tolerance, open and empathetic communication, compromise, the formation of inclusive family rituals, and the arrangement of space and time. The socio-cultural context of Tana Toraja, along with its family and tolerance values , also influences the dynamics of this negotiation. Minimizing interfaith marriages internally involves several key strategies: 1) Parents or families play a crucial role in fortifying their children through controlling and teaching Islamic beliefs (aqidah) and morals. Moreover, 2) the Office of Religious Affairs (KUA, Kantor Urusan Agama) can optimize the role of Islamic Religious Counselors in each village by collaborating with Mosque Imams to provide counseling on the importance of marriage registration and educate about the potential risks associated with interfaith marriages.